Akuntansi Aktiva Tetap pada PDAM Mual Na Tio Kabupaten Tapanuli Utara - kresvo hutauruk (Universitas HKBP Nommensen, 2023)
The purpose of this study was to determine whether the accounting treatment of fixed assets at the Regional Drinking Water Company (PDAM) Mual Na Tio North Tapanuli Regency is in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) Chapter 15. This research uses Primary data, namely data obtained or collected by researchers directly from the research site in the form of financial statements in 2020, and the data analysis method used in this research is descriptive and comparative analysis method. The steps taken in this research is to collect the supporting data needed to ensure the accuracy and correctness of the recording of assets, then analysed the accounting treatment of fixed assets and compared the accounting treatment of fixed assets with the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) to see the suitability of the accounting treatment of fixed assets made by the company with the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). The results of this study indicate that the accounting treatment of fixed assets at the Regional Drinking Water Company (PDAM) Mual Na Tio North Tapanuli Regency has not fully implemented the Accounting Standards for Entities Without Public Accountability (SAK - ETAP) Chapter 15 in preparing the company's financial statements, this can be seen from the recording of fixed assets on land and buildings. Where the fixed asset value of the building is not included in the Balance Sheet and Notes to Financial Statements (CALK) section of the company's fixed asset list.